A Descriptive Analysis of Cancer Screening Health Literacy Among Black Women Living with HIV in Baltimore, Maryland - Chun-An Sun; Joyline Chepkorir; Kyra Jennifer Waligora Mendez; Joycelyn Cudjoe; Hae-Ra Han (Health Literacy Research and Practice)
Background: Black women living with HIV (WLH) have the highest HIV infection rate, cervical cancer mortality, and the lowest cancer screening use compared to other groups. However, there is a gap in knowledge about cancer screening health literacy in the Black WLH population. Objective: The purpose of this study was to assess the level of cancer screening health literacy, and to identify factors associated with health literacy among Black WLH. Methods: This study used baseline data from a community-based randomized controlled trial for a health literacy intervention called CHECC-uP (community-based health literacy intervention for cancer control). We recruited a convenience sample of Black WLH (N = 123) who understand English and had no Pap testing in the prior 12 months. The outcome was cancer screening health literacy measured with a validated health literacy tool—Assessment of Health Literacy in Cancer Screening. Predictors included age, marital status, education, income, and insurance type. The association between cancer screening health literacy and predictors was assessed with multivariate logistic regression. Key Results: Almost one-half (49.6%) of study participants had a reading level at or below sixth grade. Older age (adjusted odds ratio [aOR] 1.05) and higher educational levels (aOR 5.13) were significantly associated with higher cancer screening health literacy among our sample of Black WLH in bivariate and multivariate analyses. Conclusions: Educational materials and other approaches to empower patients should be tested with patients who have low health literacy to ensure efficacy. [HLRP: Health Literacy Research and Practice. 2022;6(3):e175–e181.] Plain Language Summary: Using a cancer screening health literacy tool, we found that about one-half of the Black WLH in the study had a reading level at or below sixth grade. Age and education level were related to their reading levels among the women. Researcher and clinicians need to test educational materials and other approaches with patients who have low health literacy to make sure they work.